Strategies for enhancing the scholarship of teaching and learning among primary and secondary school teachers: a grounded theory analysis - Yong, Ping; Peng, Yuanyuan (Frontiers in Education, 2025)
IntroductionThis study explores the challenges and support needs faced by primary and secondary school teachers in enhancing their Scholarship of Teaching and Learning (SoTL).MethodsUsing a grounded theory approach, in-depth interviews were conducted with 16 teachers from City C, China. The data were systematically analyzed through open, axial, and selective coding.ResultsThe study identifies key factors influencing SoTL enhancement, including teachers’ professional development needs, policy pressures, resource constraints, and a lack of social support.DiscussionThe findings highlight the importance of strengthening teachers’ professional identity, optimizing resource allocation, establishing peer support systems, and refining educational policies. This study offers actionable strategies to support teachers’ professional growth and improve instructional practices.